2011
DOI: 10.1186/1471-2474-12-112
|View full text |Cite
|
Sign up to set email alerts
|

Subgroup analyses on return to work in sick-listed employees with low back pain in a randomised trial comparing brief and multidisciplinary intervention

Abstract: BackgroundMultidisciplinary intervention is recommended for rehabilitation of employees sick-listed for 4-12 weeks due to low back pain (LBP). However, comparison of a brief and a multidisciplinary intervention in a randomised comparative trial of sick-listed employees showed similar return to work (RTW) rates in the two groups. The aim of the present study was to identify subgroups, primarily defined by work-related baseline factors that would benefit more from the multidisciplinary intervention than from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 27 publications
2
70
0
4
Order By: Relevance
“…28,29 However, the ultimate intensity of multidisciplinary treatment remains under discussion. 8,19,28 One recent study reported 20 that both brief and multidisciplinary treatments were effective, although in different subgroups. In those without work-related yellow flags, 4 the brief intervention was sufficient, while approximately one-third of the group showed better outcomes as a result of participating in multidisciplinary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 However, the ultimate intensity of multidisciplinary treatment remains under discussion. 8,19,28 One recent study reported 20 that both brief and multidisciplinary treatments were effective, although in different subgroups. In those without work-related yellow flags, 4 the brief intervention was sufficient, while approximately one-third of the group showed better outcomes as a result of participating in multidisciplinary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ainsi Stapelfeldt et al [39] ont étudié l'efficacité de ces interventions sur le retour au travail en analysant des sous-groupes de travailleurs aux caractéristiques psychosociales différentes. Leur analyse montre que les interventions multidisciplinaires sont surtout profitables aux populations présentant un faible niveau de satisfaction professionnelle, avec des travailleurs souffrant d'exclusion, ayant peu de prise sur la planification de leur travail et évoquant des craintes de perte de leur emploi.…”
Section: Sélection De Groupes-cibleunclassified
“…[1][2][3][4][5][6][7][8] In many countries, early LBP management is emphasized when training physiotherapists (PTs) for direct access, including Great Britain, the Netherlands, Norway, Finland, the USA, Canada, and Australia. Results of surveys for early PT management of patients with LBP have been positive, from the patient's point of view, as well as with respect to the costs associated with return to work.…”
Section: Introductionmentioning
confidence: 99%